Review of Chinese species of the genus Embrikstrandia Plavilstshikov, 1931 (Coleoptera: Cerambycidae: Cerambycinae) with description of a new species - Huang, Jianhua; Zhou, Shanyi; Chen, Bin (Zootaxa, 2006)
The longicorn beetle genus Embrikstrandia Plavilstshikov is reviewed with descriptions of four Chinese species including a new species, E. pubemaculata sp. nov. from Guangxi Province. A key to the four Chinese species of the genus is presented.